Day-ahead Scheduling of Park Integrated Energy System Considering the Demand Response. Issue 1 (November 2020) - Zhang, Jing; Zhang, Peng; Liu, Chang; Dai, Kang; Lin, Jingyi; Tong, Chong
Abstract: The Park Integrated Energy System (PIES) is essential to increase the economic energy supply for the coupling of multiple energy sources. Thus, this paper firstly analyzed the integrated demand response function of park energy users, and then constructed the optimal scheduling model of PIES aiming at the economy of PIES. Finally, an improved non-dominated scheduling genetic algorithm with elite strategy (NSGA-II) was proposed to solve the optimization problem. The results show that the model can effectively solve the optimal scheduling problem of PIES, and the integrated demand response can effectively improve the economic figure of PIES.